Conceptualising Women$1 (Bs Working Livess Moving the Boundaries of Discourse - Patton, Wendy; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
Theoretical work on the career development of women has travelled a journey from critique to creation. Early work responded to and criticised a literature that focused on theorising male roles in a workplace that was conceptualised as providing vertical career paths primarily for middle class males. More recently theorists are creating new constructions and frameworks to enable a more holistic understanding of career, applicable to both women and men. These constructions include broadening the discussion from women$1 (Bs careers to women$1 (Bs working lives. This is the fifth book in the Sense Publishers Career Development Series. It features the vibrant work of contributors from around the world writing in the field of women$1 (Bs working lives. It emphasises the need to explore theoretical connections and understandings in order to facilitate a more holistic and inclusive understanding of women$1 (Bs working lives. The writers in the current volume acknowledge the changing roles of women, in both public and private spheres. Women$1 (Bs roles in paid work are changing both in their nature and type of engagement. In addition, with an ageing population, women$1 (Bs roles in care work are increasingly being extended from child care to aged care. This book provides a history of theorising about women's careers, in addition to presenting a focus on current empirical and theoretical work which contributes to understandings of women's working lives. It$1 (Bs contributions both map the current discourse and challenge future work to extend the boundaries of that discourse.s
Keywords: Education; Education; Education (general).